Os entraves na reforma do ensino médio à luz da proposta filosófico-educacional em Nietzsche - Barbosa, Renê da Silva (2022)
Nietzsche's philosophical-educational perspective, in the political and cultural context in nineteenth-century Germany, presents a radical, broad and refined questioning about utilitarian educational systems, from basic education to university, dedicated to artificial training. Unlike other theoretical conceptions, which keep life in its entirety far from analysis, the German philosopher developed reflections on various themes - religion, politics, science, marriage, friendship, climate, State, democracy, socialism, liberalism, aristocracy -, among so many other topics. His diagnosis in relation to modern society, totalitarian understandings, social bodies, which imprison the will to power in the human person, is self-overcoming of scientific and moral standards and, in general, of institutions that level the formation of individuals. The dynamism of philosophical activities, the affirmation of life in the midst of human tragedy, the incessant search for renewal and deepening of crucial themes, reveal Nietzsche's provocative character, in his approach to questioning static worldviews. Faced with educational weaknesses in a politically and morally complex situation, the purpose of the research is to analyze the reform of high school in light of the philosophical-educational perspective in Nietzsche. The research has the following problem: The research has the following problem: how is educational thinking in Nietzsche able to illuminate the proposed Law on The Reform of High School? The methodology used is bibliographical and documentary research, with an analytical-reflective nature, particularly anchored in Nietzsche's works, namely, Writings on education (2011), Writings on Politics: ideologies and aristocratism. V. I (2007), Writings on Politics: the small and the big politics. V. II (2007). As a theoretical foundation on education and secondary education reform, the following works are highlighted: CUNHA (2017, 1999, 2001, 2005), SANDRI (2016, 2017), GONÇALVES (2017), FREITAS (2012, 2014, 2106), SAVIANI, (2004, 2008, 2009, 2013, 2020), KUENZER (2020), MOTTA; FRIGOTTO (2017), among others. The investigations indicated that Nietzsche brings a provocation to problematize the challenges of education in the democratic context, especially the reform of high school, educational policies, the school curriculum, teacher education. Studies reveal that art of creation in Nietzsche's thought evokes the elevation of educational, political or cultural weakness through the affirmative posture on negative values. Therefore, the philosopher stresses that the function of democracy is precisely to guarantee an authentic education for human development.(AU)